Salt tolerance and functional traits of Morella pensylvanica and Vaccinium angustifolium differ between coastal forests and barrens in Nova Scotia - Lauren Schofield; Ellie M. Goud (Flora, 2026)

Reconstructing prehistoric land cover and landuse in complex ‘blue-green’ landscapes - Kimberley L. Davies; M. Jane Bunting; Willem Koster; Nicki J. Whitehouse; Michelle Farrell; Henry Chapman; Jason R. Kirby; J. Edward Schofield; Phil Barratt; Benjamin Gearey; Nika Shilobod (Vegetation History and Archaeobotany, 2026)

Melt-bearing nodules from Tenerife reveal magma reservoir diversity prior to caldera-forming eruptions - Emma L Horn; Rex N Taylor; Thomas M Gernon; Michael J Stock; Katherine E Schofield; Richard J. Brown; Victoria C Smith; Danielle McLean (Contributions to Mineralogy and Petrology, 2026)
Partially crystalline nodules are occasionally discovered within breccias linked to large ignimbrite-forming eruptions, providing evidence of the fragmentation of the plutonic reservoir and conduit system during such eruptions. These nodules offer valuable insights into the magmatic systems fuelling these highly explosive volcanoes. On Tenerife, crystal-rich samples containing interstitial melt are preserved in several Plinian eruption deposits spanning over ~ 1.8 million years, but the crustal architecture and interactions between magma reservoirs beneath the island remain poorly understood. This study focuses on explosively fragmented juvenile nodules from Tenerife’s pyroclastic deposits, which provide snapshots of the mush reservoir preceding caldera-forming events. Petrological, major element and trace element analyses were conducted on juvenile nodules from five major caldera-forming eruptions: Caleta (221 ka), Fasnia (312 ka), San Juan (1.50 Ma), Morteros (~ 1.70 Ma), and Gaviotas (1.84 Ma). These nodules preserve a range of crystallisation stages within Tenerife’s alkaline magmatic system, uniquely containing interstitial groundmass that existed in a supra-solidus state at the time of eruption, with an average melt content of ~ 25 vol%. Despite macro-mineralogical variability between eruptions, the juvenile nodules exhibit consistent basanite interstitial groundmass chemistry and lithologies, suggest that the mafic mush reservoir beneath Tenerife has remained both chemically and petrologically stable over ~ 1.8 million years. This study provides a new perspective on the stability of the mafic mush reservoir beneath Tenerife, highlighting its persistent role in the volcano’s magmatic plumbing system. The chemical consistency of the mush contrasts with the episodic mobilisation and more chemically diverse evolved phonolite melts, underscoring the importance of understanding mid-crustal processes leading to explosive eruptions. These findings provide evidence for a long-lived, stable mush reservoir and a new perspective on the compositional makeup of the crystal-mush reservoirs at defined points in time, enhancing our temporal understanding of ocean island volcanoes and their crustal magma mush reservoirs.

Multidecadal increase in microbial biomass and production along the western Antarctic Peninsula - Hugh W. Ducklow; Oscar M. Schofield; Sharon E. Stammerjohn; David L. Kirchman (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Development of a PCR ‐Based Assay for Assessing Biosecurity Risk of Extruded Feed for White Spot Disease - Hung Nam Mai; Paul J. Schofield; Wendy M. Sealey; Tressa M. Baker; Arun K. Dhar (Journal of Fish Diseases, 2025)
Formulated aquafeed has been a primary driver for the growth of the aquaculture industry worldwide. However, formulated feed may pose a biosecurity risk if they are not proven to be free of infectious pathogens. Unforetunately, recent PCR methods cannot differentiate an infectious pathogen from an inactivated genomic fragment of the corresponding pathogen. Considering the lack of an immortal cell line in crustaceans, we developed a conventional one‐step PCR assay that can be used to screen formulated aquafeed. As a proof‐of‐principle, extruded feed containing (w/w) 0.0%, 0.2% and 2% WSSV‐infected shrimp meals were prepared and screened using a one‐step conventional PCR and a real‐time PCR targeting the WSSV DNA polymerase gene. The results were compared to the WOAH‐recommended nested‐ and real‐time PCR for WSSV. The newly developed and the WOAH‐recommended real‐time PCR methods detected WSSV DNA in the extruded feed. Among three primer sets used in one‐step conventional PCR, two provided successful WSSV amplification with amplicon size of 334 and 341 bp, respectively. The primer set that generated an amplicon of 980 bp, as well as the WOAH‐recommended nested PCR, did not amplify WSSV in the extruded feed. The one‐step conventional PCR generating a 980 bp amplicon is highly specific in detecting WSSV, and the limit of detection is 100 copies. When WSSV‐spiked extruded feed was fed to Specific Pathogen Free (SPF) Penaeus vannamei shrimp, it did not cause disease, as determined by histopathology and PCR assays, indicating that the WSSV‐spiked extruded feed does not contain infectious virus. We propose that real‐time PCR, for its high throughput ability, could be used for initial screening, and any samples that test positive for WSSV should be further tested using a one‐step conventional PCR that amplifies a 980 bp amplicon. This will provide a much‐needed practical solution for biosecurity assessment of formulated aquafeed for WSD until a crustacean cell line is available for screening infectious WSSV.

Influence of traffic volume on mammal beta diversity within the road effect zone - Thomas J. Yamashita; David B. Wester; Zachary M. Wardle; Daniel G. Scognamillo; Landon R. Schofield; Michael E. Tewes; John H. Young; Jason V. Lombardi (Biological Conservation, 2025)

Automated assessment of KI-67 proliferation index of canine cutaneous mast tumours using deep learning - R. Fox; M. Dobromylskyj; A. Ide; O. Davies; K. Boyd; I. Schofield; A. Oksman; E. Vaara (Journal of Comparative Pathology, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Cryptic variation in the sooty albatross Phoebetria fusca: genetic and morphological differences between Atlantic and Indian Ocean birds - Dilini K. Abeyrama; Michelle M. Risi; Maelle Connan; Peter G. Ryan; Christopher W. Jones; Trevor Glass; Alexis M. Osborne; Antje Steinfurth; Andy Schofield; Pierre Pistorius; Danielle Keys; Yves Cherel; et al. (Conservation Genetics, 2025)

Quantifying Virtual Field Trip Efficiency - J. H. Pugsley; J. A. Howell; A. J. Hartley; S. J. Buckley; M. Chmielewska; N. Naumann; N. J. Schofield; R. Brackenridge (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)
The efficiency of virtual field trips (VFTs) compared to their physical counterparts, is often regarded as one of their key benefits. Virtual field trips are typically more time, cost and environmentally efficient and logistically easier to plan and execute. This is largely due to the lack of travel, however, the nature of these efficiencies, which is essential for deciding whether a trip should be virtual, physical or blended, have not previously been quantified. Here we present a quantitative evaluation of several measures of efficiency, using data from a like-for-like comparison between 10 day long virtual and physical field trips to Utah, USA, from the University of Aberdeen, UK. For this case study, our results demonstrate that virtual field trips are more efficient across all the categories of time, cost, environmental impact, and logistics. In addition to saved air travel days at the start and end of the physical trip, a further 33.3% of the time on the physical field trip was spent travelling (walking and driving). This time saving allowed an additional 16 localities to be visited on the virtual field trip. The virtual field trip localities also ran in an order that best suited the geological narrative rather than their geographic location which the physical field trip was restricted by. Flights and driven kilometres for the physical trip produced c. 4 t of carbon dioxide equivalent (CO 2 ) per student. The virtual trip produce <1% of the CO 2 and was comparable to a typical teaching week, making it significantly more environmentally efficient. The cost of the virtual trip was negligible compared to that of the physical trip (saving up to £ 3000 GBP per student). These findings were compared to the fulfilment of learning outcomes, quantified primarily through questionnaires, the student responses suggest that the PFT and VFT perceptions of learning outcomes were generally comparable. Efficiency is not the only measure of a successful field trip, with other parameters such as social cohesion and embodiment within the outdoor environment that must also be considered when planning a field trip. Therefore, the authors do not advocate or support an abandonment of physical field trips. Rather, this study aims to provide a first attempt to quantify efficiency to inform decision making when planning field training.

Far infrared radiative properties of Mars atmospheric aerosols and their application to Mars Climate Sounder retrievals of aerosol profiles, aerosol columns and surface temperatures - A. Kleinböhl; D.M. Kass; M. Schreier; S. Piqueux; S. Suzuki; J.H. Shirley; L. Chen; J.T. Schofield (Icarus, 2024)

Mars thermal inertia and surface temperatures by the Mars Climate Sounder - Sylvain Piqueux; David M. Kass; Armin Kleinböhl; Marek Slipski; Paul O. Hayne; Daniel J. McCleese; John T. Schofield; Nicholas Heavens (Icarus, 2024)

The thermal expansion of Ti-substituted CaAl12O19 - Paul F. Schofield; Andrew J. Berry; Patricia M. Doyle; Kevin S. Knight (Physics and Chemistry of Minerals, 2024)
CaAl 12 O 19 , which can incorporate Ti as both Ti 3+ and Ti 4+ (charge coupled substitution with Mg 2+ ), is one of the first minerals to condense from a gas of solar composition and is used as a ceramic. It is variously known as hibonite, calcium hexaluminate (CaO.6Al 2 O 3 ), and CA 6 . The lattice parameters and unit cell volumes of Ti-substituted hibonite ( P 6 3 / mmc ) with the formulae CaAl 11.8 Ti 3+ 0.2 O 19 and CaAl 9.8 Ti 3+ 0.54 Mg 0.83 Ti 4+ 0.83 O 19 were determined as a function of temperature from ~ 10 to 275 K by neutron powder diffraction. The thermal expansion is highly anisotropic with the expansion in c a factor of ~ 5 greater than that in a . The change in a is approximately equal for the two compounds whereas the change in c is almost 50% larger for CaAl 11.8 Ti 3+ 0.2 O 19 . CaAl 11.8 Ti 3+ 0.2 O 19 also exhibits negative thermal expansion between 10 and 70 K. The change in unit cell volume with temperature of both compositions is well described by a two term Einstein expression. The large change in c is consistent with substitution of Ti onto the M2 and M4 sites of the R-block structural unit.

Thoracolumbar hydrated nucleus pulposus extrusion and intervertebral disc extrusion in dogs: Comparison of clinical presentation and magnetic resonance imaging findings - E. Alcoverro; I. Schofield; S. Spinillo; A. Tauro; M. Ruggeri; M. Lowrie; S.A. Gomes (The Veterinary Journal, 2024)

Biochar improves fertility in waste derived manufactured soils, but not resilience to climate change - Jennifer M. Rhymes; Daniel Evans; Giuliano Laudone; H. Kate Schofield; Ellen Fry; Mark F. Fitzsimons (Science of The Total Environment, 2024)

The contamination of in situ archaeological remains: A pilot analysis of microplastics in sediment samples using μFTIR - Jeanette M. Rotchell; Freija Mendrik; Emma Chapman; Paul Flintoft; Ian Panter; Giulia Gallio; Christine McDonnell; Catriona R. Liddle; David Jennings; John Schofield (Science of The Total Environment, 2024)

Construction of relatedness matrices in autopolyploid populations using low-depth high-throughput sequencing data - Timothy P. Bilton; Sanjeev Kumar Sharma; Matthew R. Schofield; Michael A. Black; Jeanne M. E. Jacobs; Glenn J. Bryan; Ken G. Dodds (Theoretical and Applied Genetics, 2024)
Key message An improved estimator of genomic relatedness using low-depth high-throughput sequencing data for autopolyploids is developed. Its outputs strongly correlate with SNP array-based estimates and are available in the package GUSrelate. Abstract High-throughput sequencing (HTS) methods have reduced sequencing costs and resources compared to array-based tools, facilitating the investigation of many non-model polyploid species. One important quantity that can be computed from HTS data is the genetic relatedness between all individuals in a population. However, HTS data are often messy, with multiple sources of errors (i.e. sequencing errors or missing parental alleles) which, if not accounted for, can lead to bias in genomic relatedness estimates. We derive a new estimator for constructing a genomic relationship matrix (GRM) from HTS data for autopolyploid species that accounts for errors associated with low sequencing depths, implemented in the R package GUSrelate. Simulations revealed that GUSrelate performed similarly to existing GRM methods at high depth but reduced bias in self-relatedness estimates when the sequencing depth was low. Using a panel consisting of 351 tetraploid potato genotypes, we found that GUSrelate produced GRMs from genotyping-by-sequencing (GBS) data that were highly correlated with a GRM computed from SNP array data, and less biased than existing methods when benchmarking against the array-based GRM estimates. GUSrelate provides researchers with a tool to reliably construct GRMs from low-depth HTS data.

The oxidation state of titanium in silicate melts - Andrew J. Berry; Patricia M. Doyle; Paul F. Schofield; Laura A. Miller; Charles Le Losq; Antony D. Burnham; J. Fred W. Mosselmans (Geochimica et Cosmochimica Acta, 2024)

The Southern Ocean carbon and climate observations and modeling (SOCCOM) project: A review - Jorge L. Sarmiento; Kenneth S. Johnson; Lionel A. Arteaga; Seth M. Bushinsky; Heidi M. Cullen; Alison R. Gray; Roberta M. Hotinski; Tanya L. Maurer; Matthew R. Mazloff; Stephen C. Riser; Joellen L. Russell; Oscar M. Schofield; et al. (Progress in Oceanography, 2023)

Cyclical prey shortages for a marine polar predator driven by the interaction of climate change and natural climate variability - Amanda C. Lohmann; Joseph P. Morton; Oscar M. Schofield; Douglas P. Nowacek (Limnology and Oceanography, 2023)
Between 1992 and 2018, the breeding population of Adélie penguins around Anvers Island, Antarctica declined by 98%. In this region, natural climate variability drives five‐year cycling in marine phytoplankton productivity, leading to phase‐offset five‐year cycling in the size of the krill population. We demonstrate that the rate of change of the Adélie breeding population also shows five‐year cycling. We link this population response to cyclical krill scarcity, a phenomenon which appears to have arisen from the interaction between climate variability and climate change trends. Modeling suggests that, since at least 1980, natural climate variability has driven cycling in this marine system. However, anthropogenic climate change has shifted conditions so that fewer years in each cycle now prompt strong krill recruitment, triggering intervals of krill scarcity that result in drastic declines in Adélie penguins. Our results imply that climate change can amplify the impacts of natural climate oscillations across trophic levels, driving cycling across species and disrupting food webs. The findings indicate that climate variability plays an integral role in driving ecosystem dynamics under climate change.

Priorities for Mediterranean marine turtle conservation and management in the face of climate change - Antonios D. Mazaris; Charalampos Dimitriadis; Maria Papazekou; Gail Schofield; Aggeliki Doxa; Anastasia Chatzimentor; Oguz Turkozan; Stelios Katsanevakis; Aphrodite Lioliou; Sara Abalo-Morla; Mustapha Aksissou; Antonella Arcangeli; et al. (Journal of Environmental Management, 2023)

Remote sensing of sea surface glacial meltwater on the Antarctic Peninsula shelf - B. Jack Pan; Michelle M. Gierach; Michael P. Meredith; Rick A. Reynolds; Oscar Schofield; Alexander J. Orona (Frontiers in Marine Science, 2023)
Glacial meltwater is an important environmental variable for ecosystem dynamics along the biologically productive Western Antarctic Peninsula (WAP) shelf. This region is experiencing rapid change, including increasing glacial meltwater discharge associated with the melting of land ice. To better understand the WAP environment and aid ecosystem forecasting, additional methods are needed for monitoring and quantifying glacial meltwater for this remote, sparsely sampled location. Prior studies showed that sea surface glacial meltwater (SSGM) has unique optical characteristics which may allow remote sensing detection via ocean color data. In this study, we develop a first-generation model for quantifying SSGM that can be applied to both spaceborne (MODIS-Aqua) and airborne (PRISM) ocean color platforms. In addition, the model was prepared and verified with one of the more comprehensive in-situ stable oxygen isotope datasets compiled for the WAP region. The SSGM model appears robust and provides accurate predictions of the fractional contribution of glacial meltwater to seawater when compared with in-situ data ( r = 0.82, median absolute percent difference = 6.38%, median bias = −0.04), thus offering an additional novel method for quantifying and studying glacial meltwater in the WAP region.

DeepVerge: Classification of roadside verge biodiversity and conservation potential - Andrew Perrett; Harry Pollard; Charlie Barnes; Mark Schofield; Lan Qie; Petra Bosilj; James M. Brown (Computers, Environment and Urban Systems, 2023)

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

High polygenic risk score for exceptional longevity is associated with a healthy metabolic profile - Mary Revelas; Anbupalam Thalamuthu; Anna Zettergren; Christopher Oldmeadow; Jenna Najar; Nazib M. Seidu; Nicola J. Armstrong; Carlos Riveros; John B. Kwok; Peter R. Schofield; Julian N. Trollor; Margda Waern; et al. (GeroScience, 2023)
Healthy metabolic measures in humans are associated with longevity. Dysregulation leads to metabolic syndrome (MetS) and negative health outcomes. Recent exceptional longevity (EL) genome wide association studies have facilitated estimation of an individual’s polygenic risk score (PRS) for EL. We tested the hypothesis that individuals with high ELPRS have a low prevalence of MetS. Participants were from five cohorts of middle-aged to older adults. The primary analyses were performed in the UK Biobank (UKBB) ( n = 407,800, 40–69 years). Replication analyses were undertaken using three Australian studies: Hunter Community Study ( n = 2122, 55–85 years), Older Australian Twins Study ( n = 539, 65–90 years) and Sydney Memory and Ageing Study ( n = 925, 70–90 years), as well as the Swedish Gothenburg H70 Birth Cohort Studies ( n = 2273, 70–93 years). MetS was defined using established criteria. Regressions and meta-analyses were performed with the ELPRS and MetS and its components. Generally, MetS prevalence (22–30%) was higher in the older cohorts. In the UKBB, high EL polygenic risk was associated with lower MetS prevalence (OR = 0.94, p = 1.84 × 10 –42 ) and its components ( p < 2.30 × 10 – 8 ). Meta-analyses of the replication cohorts showed nominal associations with MetS ( p = 0.028) and 3 MetS components ( p < 0.05). This work suggests individuals with a high polygenic risk for EL have a healthy metabolic profile promoting longevity.

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Hourly emission inventories for air toxic emissions for eastern Australian electricity generators derived from energy distribution data - M. Garg; J. D. Silver; R. Schofield; R. G. Ryan (International Journal of Environmental Science and Technology, 2022)

Cetaceans Sightings During Research Cruises in Three Remote Atlantic British Overseas Territories - Stephanie M. Martin; Marta Soeffker; Andy Schofield; Rhys Hobbs; Trevor Glass; Simon A. Morley (Frontiers in Marine Science, 2021)
Marine mammal sightings were recorded during research cruises to three remote, mid-ocean British Overseas Territories in the South Atlantic and Southern Ocean. In March to April 2018 and 2019, the Exclusive Economic Zones (EEZs) of tropical St Helena and temperate Tristan da Cunha were surveyed. The sub-polar waters of South Georgia and the South Sandwich Islands (SGSSI) were surveyed in February to March 2019. At St Helena in 2018, five species were recorded during 11 sightings, and in 2019, four species, with one additional unidentified species, during seven sightings. Most of these sightings were of dolphin species, which are known to be resident around the Island and seamounts. In Tristan da Cunha in 2018, a total of five identified and one unidentified species were recorded during six sightings, half of which were associated with the Islands or seamounts. In 2019, due to rough weather, no sightings were recorded in the Tristan da Cunha waters. Around SGSSI, 162 sightings of 236 cetaceans were made in 2019, mostly of baleen whales, with seven species identified with certainty. Sightings around the southern South Sandwich Islands included beaked whales and large dolphins, whereas baleen whales dominated in the northern South Sandwich Islands. These results provide new data for rarely surveyed regions, helping to build a spatial picture of important areas for marine mammals, which will help inform marine spatial protection strategies.

Low diversity of a key phytoplankton group along the West Antarctic Peninsula - Michael S. Brown; Jeff S. Bowman; Yajuan Lin; Colette J. Feehan; Carly M. Moreno; Nicolas Cassar; Adrian Marchetti; Oscar M. Schofield (Limnology and Oceanography, 2021)
The West Antarctic Peninsula (henceforth “Peninsula”) is experiencing rapid warming and melting that is impacting the regional marine food web. The primary phytoplankton groups along the Peninsula are diatoms and cryptophytes. Relative to diatoms, there has been little focus on regional cryptophytes, and thus our understanding of their diversity and ecology is limited, especially at the species level. This gap is important, as diatoms and cryptophytes play distinct roles in the regional marine food web and biogeochemistry. Here, we use a phylogenetic placement approach with 18S rRNA gene amplicon sequence variants to assess surface ocean cryptophyte diversity and its drivers at a high taxonomic resolution along the Peninsula. Data were collected over 5 years (2012–2016) during the regional research cruises of the Palmer Long‐Term Ecological Research program. Our results indicate that there are two major cryptophyte taxa along the Peninsula, consisting of distinct Geminigera spp., which in aggregate always comprise nearly 100% of the cryptophyte community (indicating low taxa evenness). The primary taxon dominates the cryptophyte community across all samples/years, which span a broad range of oceanographic conditions. A shift in cryptophyte community composition between a lower (higher) primary (secondary) taxon percentage is associated with distinct oceanographic conditions, including lower (higher) temperature, salinity, nutrients, and cryptophyte relative abundance (phytoplankton biomass and diatom relative abundance). These results emphasize the need for a full characterization of the ecology of these two taxa, as it is predicted that cryptophytes will increase along the Peninsula given projections of continued regional environmental change.

Palynological evidence for pre-agricultural reindeer grazing and the later settlement history of the Lycksele region, northern Sweden - Ilse M. Kamerling; J. Edward Schofield; Kevin J. Edwards (Archaeological and Anthropological Sciences, 2021)
Analyses of high-resolution pollen data, coprophilous fungal spores, microscopic charcoal and sedimentology, combined with radiocarbon dating, allow the assessment of the impact of Sami and Nordic land use in the region surrounding the winter market town of Lycksele in northern Sweden. Such winter markets were established by the Crown during the seventeenth century AD to control the semi-nomadic movements of the Sami who traded here with Finnish settlers and were also taxed and educated. Little is known about Sami and Nordic co-existence beyond these market places, mainly due to a lack of archaeological evidence relating to Sami activity. Vegetation and land-use changes in the region between ~ AD 250 and 1825 reveal no signal for pre-seventeenth century agricultural activity, but the coprophilous fungal spore records suggest the increased regional presence of grazing herbivores (possibly reindeer) between ~ AD 800 and 1100. Sami activity in the parish of Lycksele has been suggested by rich metal finds dated to ~ AD 1000–1350 and they may have been attracted by an abundance of reindeer.

Crumbling Reefs and Cold-Water Coral Habitat Loss in a Future Ocean: Evidence of “Coralporosis” as an Indicator of Habitat Integrity - Sebastian J. Hennige; Uwe Wolfram; Leslie Wickes; Fiona Murray; J. Murray Roberts; Nicholas A. Kamenos; Sebastian Schofield; Alexander Groetsch; Ewa M. Spiesz; Marie-Eve Aubin-Tam; Peter J. Etnoyer (Frontiers in Marine Science, 2020)

Testing the Canyon Hypothesis: Evaluating light and nutrient controls of phytoplankton growth in penguin foraging hotspots along the West Antarctic Peninsula - Filipa Carvalho; Jessica N. Fitzsimmons; Nicole Couto; Nicole Waite; Maxim Gorbunov; Josh Kohut; Matthew J. Oliver; Robert M. Sherrell; Oscar Schofield (Limnology and Oceanography, 2020)
Biological hotspots along the West Antarctic Peninsula (WAP) are characterized by high phytoplankton productivity and biomass as well as spatially focused penguin foraging activity. While unique physical concentrating processes were identified in one of these hotspots, understanding the mechanisms driving the blooms at these locations is of high importance. Factors posited to explain the blooms include the upwelling of macronutrient‐ and micronutrient‐enriched modified Upper Circumpolar Deep Water (mUCDW) and the depth of the mixed layer influencing overall light availability for phytoplankton. Using shipboard trace‐metal clean incubation experiments in three different coastal biological hotspots spanning a north‐south gradient along the WAP, we tested the Canyon Hypothesis (upwelling) for enhanced phytoplankton growth. Diatoms dominated the Southern region, while the Northern region was characterized by a combination of diatoms and cryptophytes. There was ample concentration of macronutrients at the surface and no phytoplankton growth response was detected with the addition of nutrient‐enriched mUCDW water or iron solution to surface waters. For all treatments, addition of mUCDW showed no enhancement in phytoplankton growth, suggesting that local upwelling of nutrient‐enriched deep water in these hotspots was not the main driver of high phytoplankton biomass. Furthermore, the dynamics in the photoprotective pigments were consistent with the light levels used during these incubations showing that phytoplankton are able to photoacclimate rapidly to higher irradiances and that in situ cells are low light adapted. Light availability appears to be the critical variable for the development of hotspot phytoplankton blooms, which in turn supports the highly productive regional food web.

Delivering Sustained, Coordinated, and Integrated Observations of the Southern Ocean for Global Impact - Louise Newman; Petra Heil; Rowan Trebilco; Katsuro Katsumata; Andrew Constable; Esmee van Wijk; Karen Assmann; Joana Beja; Phillippa Bricher; Richard Coleman; Daniel Costa; Steve Diggs; et al. (Frontiers in Marine Science, 2019)

Characterisation of the NRF2 transcriptional network and its response to chemical insult in primary human hepatocytes: implications for prediction of drug-induced liver injury - Ian M. Copple; Wouter den Hollander; Giulia Callegaro; Fiona E. Mutter; James L. Maggs; Amy L. Schofield; Lucille Rainbow; Yongxiang Fang; Jeffrey J. Sutherland; Ewa C. Ellis; Magnus Ingelman-Sundberg; Stephen W. Fenwick; et al. (Archives of Toxicology, 2019)

Generation of transgenic goats by pronuclear microinjection: a retrospective analysis of a commercial operation (1995–2012) - W. Gavin; S. Blash; N. Buzzell; D. Pollock; L. Chen; N. Hawkins; J. Howe; K. Miner; J. Pollock; C. Porter; M. Schofield; Y. Echelard; et al. (Transgenic Research, 2018)

Complex movement patterns by foraging loggerhead sea turtles outside the breeding season identified using Argos‐linked Fastloc‐Global Positioning System - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Kostas Papafitsoros; Graeme C. Hays (Marine Ecology, 2018)
We used Argos‐linked Fastloc‐Global Positioning System (Argos‐linked Fastloc‐GPS) satellite tags to investigate how loggerhead sea turtles use neritic foraging habitats at multiple scales. Out of 24 turtles, six individuals used more than one foraging site, with all sites being separated by >25 km. These six individuals used up to four sites, remaining at each site for a mean of 150 days and returning to the same site a minimum of 52 days later. The other 18 turtles remained in a single site. The area within sites was not used uniformly, with 15 out of 24 turtles exhibiting complex movement patterns within and amongst up to five focal patches, which were typically 0.1–5.0 km apart within a single site. Movements between sites and patches might sometimes have reflected overwintering behaviour; however, similar movement patterns occurred at multiple times of the year, suggesting other factors were also involved. Use of multiple sites and patches might be driven by differences in resource availability, such as food and/or night‐time refuges, competition, or exploratory movement to investigate or locate alternative patches. We confirmed competition via direct visual observations of aggressive interactions between individuals at one foraging patch. Our results illustrate the importance of standardizing data to the same number of locations per day and night to accurately delineate key areas used by turtles or for evidence‐based marine protected area planning.

Improving Fab’ fragment retention in an autonucleolytic Escherichia coli strain by swapping periplasmic nuclease translocation signal from OmpA to DsbA - Desmond M. Schofield; Ernestas Sirka; Eli Keshavarz-Moore; John M. Ward; Darren N. Nesbeth (Biotechnology Letters, 2017)

Vagrant leopard seal at Tristan da Cunha Island, South Atlantic - M. N. Bester; W. A. Bester; M. Wege; R. A. Schofield; T. A. Glass (Polar Biology, 2017)

Fastloc-GPS reveals daytime departure and arrival during long-distance migration and the use of different resting strategies in sea turtles - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Nicole Esteban; Graeme C. Hays (Marine Biology, 2017)

High-resolution palynology reveals the land use history of a Sami renvall in northern Sweden - Ilse M. Kamerling; J. Edward Schofield; Kevin J. Edwards; Kjell-Åke Aronsson (Vegetation History and Archaeobotany, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Salinity and temperature tolerance of an emergent alien species, the Amazon fish Astronotus ocellatus - Silvia M. M. Gutierre; Pamela J. Schofield; Viviane Prodocimo (Hydrobiologia, 2016)

Non-specific symbiotic germination of Cynorkis purpurea (Thouars) Kraezl., a habitat-specific terrestrial orchid from the Central Highlands of Madagascar - M. Rafter; K. Yokoya; E. J. Schofield; L. W. Zettler; V. Sarasan (Mycorrhiza, 2016)

The biogeographical status of Alnus crispa (Ait.) Pursch in sub-Arctic southern Greenland: Do pollen records indicate local populations during the past 1500 years? - Paul M. Ledger; Kevin J. Edwards; J. Edward Schofield (Polar Biology, 2016)

Phylogenetic and ecological factors impact the gut microbiota of two Neotropical primate species - Katherine R. Amato; Rodolfo Martinez-Mota; Nicoletta Righini; Melissa Raguet-Schofield; Fabiana Paola Corcione; Elisabetta Marini; Greg Humphrey; Grant Gogul; James Gaffney; Elijah Lovelace; LaShanda Williams; Albert Luong; et al. (Oecologia, 2016)

Identification and analysis of the bacterial endosymbiont specialized for production of the chemotherapeutic natural product ET ‐743 - Michael M. Schofield; Sunit Jain; Daphne Porat; Gregory J. Dick; David H. Sherman (Environmental Microbiology, 2015)
Summary Ecteinascidin 743 ( ET ‐743, Y ondelis) is a clinically approved chemotherapeutic natural product isolated from the Caribbean mangrove tunicate E cteinascidia turbinata . Researchers have long suspected that a microorganism may be the true producer of the anticancer drug, but its genome has remained elusive due to our inability to culture the bacterium in the laboratory using standard techniques. Here, we sequenced and assembled the complete genome of the ET ‐743 producer, C andidatus Endoecteinascidia frumentensis, directly from metagenomic DNA isolated from the tunicate. Analysis of the ∼631 kb microbial genome revealed strong evidence of an endosymbiotic lifestyle and extreme genome reduction. Phylogenetic analysis suggested that the producer of the anti‐cancer drug is taxonomically distinct from other sequenced microorganisms and could represent a new family of Gammaproteobacteria. The complete genome has also greatly expanded our understanding of ET ‐743 production and revealed new biosynthetic genes dispersed across more than 173 kb of the small genome. The gene cluster's architecture and its preservation demonstrate that the drug is likely essential to the interactions of the microorganism with its mangrove tunicate host. Taken together, these studies elucidate the lifestyle of a unique, and pharmaceutically important microorganism and highlight the wide diversity of bacteria capable of making potent natural products.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Analyzing gene expression data in mice with the Neuro Behavior Ontology - Robert Hoehndorf; John M. Hancock; Nigel W. Hardy; Ann-Marie Mallon; Paul N. Schofield; Georgios V. Gkoutos (Mammalian Genome, 2014)

A Longman's beaked whale ( Indopacetus pacificus ) strands in Maui, Hawaii, with first case of morbillivirus in the central Pacific - Kristi L. West; Susan Sanchez; David Rotstein; Kelly M. Robertson; Sophie Dennison; Gregg Levine; Nicole Davis; David Schofield; Charles W. Potter; Brenda Jensen (Marine Mammal Science, 2013)

Neuronal fiber bundle lengths in healthy adult carriers of the ApoE4 allele: A quantitative tractography DTI study - Lauren E. Salminen; Peter R. Schofield; Elizabeth M. Lane; Jodi M. Heaps; Kerrie D. Pierce; Ryan Cabeen; David H. Laidlaw; Erbil Akbudak; Thomas E. Conturo; Stephen Correia; Robert H. Paul (Brain Imaging and Behavior, 2013)

Palynology supports ‘ O ld N orse’ introductions to the flora of G reenland - J. Edward Schofield; Kevin J. Edwards; Egill Erlendsson; Paul M. Ledger (Journal of Biogeography, 2013)
Aim This paper integrates pollen‐analytical data from sites across southern G reenland to revisit the debate regarding which plants may have been introduced during the N orse colonization or landnám c . ad 985. Location Palynological data are drawn from 14 sites (lakes and mires) located within the former E astern S ettlement of N orse G reenland ( c . 60.9° N, 45.5° W). Methods Maps are presented displaying palynological data for three taxa ( R umex acetosella , P olygonum aviculare and A chillea millefolium ), which earlier scholars have argued are ‘Old Norse’ anthropochores. The maps display pollen frequencies at regular ( c . 100‐year) intervals across a period ( ad 800–1500) encompassing N orse settlement. Results Maps for c . ad 800 and 900 (prior to N orse arrival) display the taxa as locally absent, with the appearance and expansion of their pollen at multiple sites from c . ad 1000 ( landnám ) providing support for the assumption that each taxon arrived with the first settlers. A general and widespread decline in pollen frequencies for these ‘Old Norse’ elements on the c. ad 1500 map (following N orse abandonment) demonstrates a close connection between these plants and a cultural landscape that was shaped and maintained predominantly via animal husbandry. Main conclusions Patterns emerging from this exercise may initiate wider debates related to the pattern and character of the N orse colonization of G reenland. It is suggested that differences in the function or role of farm sites could have led to the creation of greater areas of favourable habitat for ‘ O ld N orse’ flora in some locations relative to others, and that uneven patterns of colonization and the spread of ‘ O ld N orse’ plants might be explained if their introduction – presumably from Iceland – first occurred at only a few locations.

Gene-microRNA interactions associated with antipsychotic mechanisms and the metabolic side effects of olanzapine - Danielle M. Santarelli; Bing Liu; Carlotta E. Duncan; Natalie J. Beveridge; Paul A. Tooney; Peter R. Schofield; Murray J. Cairns (Psychopharmacology, 2013)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Leaf-cutter ants with worn mandibles cut half as fast, spend twice the energy, and tend to carry instead of cut - Robert M. S. Schofield; Kristen D. Emmett; Jack C. Niedbala; Michael H. Nesson (Behavioral Ecology and Sociobiology, 2011)

Architecture of the Oman–UAE ophiolite: evidence for a multi-phase magmatic history - K. M. Goodenough; M. T. Styles; D. Schofield; R. J. Thomas; Q. C. Crowley; R. M. Lilly; J. McKervey; D. Stephenson; J. N. Carney (Arabian Journal of Geosciences, 2010)

Tolerance of nonindigenous cichlid fishes (Cichlasoma urophthalmus, Hemichromis letourneuxi) to low temperature: laboratory and field experiments in south Florida - Pamela J. Schofield; William F. Loftus; Robert M. Kobza; Mark I. Cook; Daniel H. Slone (Biological Invasions, 2010)

Gating mechanisms in Cys-loop receptors - Jennie M. E. Cederholm; Peter R. Schofield; Trevor M. Lewis (European Biophysics Journal, 2009)

Genetic polymorphism in ornithine decarboxylase and risk of breast cancer - Iain Brown; Susan Halliday; Heather Greig; Steven D. Heys; Heather M. Wallace; Andrew C. Schofield (Familial Cancer, 2009)

Mouse, man, and meaning: bridging the semantics of mouse phenotype and human disease - John M. Hancock; Ann-Marie Mallon; Tim Beck; Georgios V. Gkoutos; Chris Mungall; Paul N. Schofield (Mammalian Genome, 2009)

Synergistic applications of autonomous underwater vehicles and the regional ocean modeling system in coastal ocean forecasting - Yi Chao; Zhijin Li; John D. Farrara; Mark A. Moline; Oscar M. E. Schofield; Sharanya J. Majumdar (Limnology and Oceanography, 2008)
The potential for using synergistic combinations of measurements from autonomous underwater vehicles (AUVs) and output from three‐dimensional numerical models for studying the central California coastal region is demonstrated. Two case studies are used to illustrate the approach. In the first, propeller‐driven AUV observations revealed a subsurface salinity minimum in northern Monterey Bay. A Regional Ocean Modeling System (ROMS) reanalysis of the three‐dimensional flow in the region suggested an offshore source for this water and particular propagation pathways from the south and west into the bay. In the second case study, the effectiveness of assimilating observations in improving the ROMS reanalysis fields is investigated. A significant improvement, especially in the salinity fields, is demonstrated through a single glider deployed outside the intensive observational domain. These results suggest that investigation of more sophisticated techniques for using data and models together is warranted. Such techniques include increasing model resolution in areas of interest identified by observing platforms and using model‐based “targeted observing” techniques to identify areas of uncertainty in the flow to guide placement of observational assets.

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

Hypoxia tolerance of two centrarchid sunfishes and an introduced cichlid from karstic Everglades wetlands of southern Florida, U.S.A. - P. J. Schofield; W. F. Loftus; M. E. Brown (Journal of Fish Biology, 2007)
In this study, the hypoxia tolerance of three Everglades fishes, two native centrarchids ( Lepomis gulosus and Lepomis marginatus ) and a recently introduced cichlid ( Hemichromis letourneuxi ), were documented. Aquatic surface respiration (ASR) thresholds were lowest for H. letourneuxi , followed by L. gulosus , then L. marginatus . The ASR thresholds for L. marginatus were within ranges reported for small, freshwater tropical fishes, while those for L. gulosus were similar to swamp‐adapted fishes. For H. letourneuxi , ASR thresholds were some of the lowest reported. All three species showed excellent tolerance of low dissolved oxygen levels when allowed access to the surface. When denied surface access, L. marginatus lost equilibrium at a higher oxygen tension than the other species. Overall, although all species easily tolerated hypoxia, H. letourneuxi appeared to be best equipped to deal with hypoxia, followed by L. gulosus , then L. marginatus . Hemichromis letourneuxi also exhibited more aggressive behaviours than the centrarchids. These results suggest that hypoxia is not likely to prevent H. letourneuxi from exploiting the seasonally inundated wetlands of south Florida while expanding its range there.

The role of functional traits and trade‐offs in structuring phytoplankton communities: scaling from cellular to ecosystem level - Elena Litchman; Christopher A. Klausmeier; Oscar M. Schofield; Paul G. Falkowski (Ecology Letters, 2007)
Trait‐based approaches to community structure are increasingly used in terrestrial ecology. We show that such an approach, augmented by a mechanistic analysis of trade‐offs among functional traits, can be successfully used to explain community composition of marine phytoplankton along environmental gradients. Our analysis of literature on major functional traits in phytoplankton, such as parameters of nutrient‐dependent growth and uptake, reveals physiological trade‐offs in species abilities to acquire and utilize resources. These trade‐offs, arising from fundamental relations such as cellular scaling laws and enzyme kinetics, define contrasting ecological strategies of nutrient acquisition. Major groups of marine eukaryotic phytoplankton have adopted distinct strategies with associated traits. These diverse strategies of nutrient utilization can explain the distribution patterns of major functional groups and size classes along nutrient availability gradients.

A DIVERGENT mtDNA LINEAGE AMONG MESOPLODON BEAKED WHALES: MOLECULAR EVIDENCE FOR A NEW SPECIES IN THE TROPICAL PACIFIC? - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; James G. Mead; Roger V. Grace; T. David Schofield (Marine Mammal Science, 2007)

CASE STUDY: MORBIDITY IN A PYGMY SPERM WHALE KOGIA BREVICEPS DUE TO OCEAN‐BOURNE PLASTIC - M. Andrew Stamper; Brent R. Whitaker; T. David Schofield (Marine Mammal Science, 2006)

The role of hydrogen bonding in the thermal expansion and dehydration of brushite, di-calcium phosphate dihydrate - P. F. Schofield; K. S. Knight; J. A. M. van der Houwen; E. Valsami-Jones (Physics and Chemistry of Minerals, 2004)

Effects of increased bedload on algal‐ and detrital‐based stream food webs: Experimental manipulation of sediment and macroconsumers - Kate A. Schofield; Catherine M. Pringle; Judy L. Meyer (Limnology and Oceanography, 2004)
Sedimentation poses a significant threat to stream ecosystems throughout the world, and increases in bedload can be especially detrimental to benthic communities. To examine how increased bedload affects algal‐ and detrital based stream communities, we manipulated sediment (via daily sediment addition to 0.25‐m 2 areas of stream bottom) and top‐down effects of macroconsumers (fishes and crayfish, via electric exclusion) in two factorial experiments, one using tiles and one using leaf packs as sampling substrates. Sediment addition had significant effects on both algal‐ and detrital‐based stream benthic communities, most notably via the alteration of macroconsumer‐mediated biotic interactions; these effects largely were due to sediment transport across the stream bottom, rather than sediment deposition. In the tile experiment, macroconsumers reduced total insect biomass and biomass of several dominant insect taxa under ambient sediment conditions. Sediment addition eliminated all macroconsumer effects except their reduction of chironomid biomass. In the leaf pack experiment, sediment addition eliminated macroconsumer effects on fungal accumulation rates; in general, however, leaf packs were not as affected by sediment addition as tiles. Direct effects of sediment addition were minimal in both experiments: algal composition was altered on tiles, while dipteran predator biomass tended to decline in leaf packs. These experiments demonstrate that small, environmentally realistic increases in bedload affect benthic communities, primarily via the alteration of macroconsumer effects. Although indirect effects of sedimentation have been examined less frequently than direct biotic responses, this study demonstrates the importance of sediment regime in determining the outcome of fish and crayfish‐mediated species interactions.

Tooth hardness increases with zinc-content in mandibles of young adult leaf-cutter ants - Robert M. S. Schofield; Michael H. Nesson; Kathleen A. Richardson (The Science of Nature, 2002)

The function of plastids in the deep‐sea benthic foraminifer, Nonionella stella - Joe Grzymski; Oscar M. Schofield; Paul G. Falkowski; Joan M. Bernhard (Limnology and Oceanography, 2002)
Curiously, the benthic foraminifer, Nonionella stella , found in the upper 3 cm of sediments collected off California at a depth of ;600 m, retains chloroplasts. We examined the origin and physiological function of the organelles within the host cell. Transmission electron micrographs, fluorescence and absorption spectra, Western blots, and enzyme assays revealed that the chloroplasts were intact and retained functionality for up to 1 year after sample collection. 16S rDNA gene sequences established that the plastids were derived from diatoms closely related to Skeletonema costatum and Odontella sinensis . Western blots of three major chloroplast proteins (ribulose bisphosphate carboxylase oxygenase [RuBisCO], the D1 protein, and the fucoxanthin chlorophyll a protein complex) confirmed that the organelle retained both nuclear and chloroplast encoded proteins, which suggests that the turnover of the plastid machinery is extremely low. Moreover, the two carboxylating enzymes examined, RuBisCO and phosphoenol pyruvate carboxylase, retained catalytic activity. Three hypotheses regarding the function of sequestered chloroplasts in deep‐sea foraminifera were considered: (1) the organelles are photosynthetic under extremely low irradiance levels, (2) the organelles utilize exogenous substrates to generate an electrochemical gradient that permits chemoautrophy in the dark, and (3) they are used for the assimilation of inorganic nitrogen. Our results suggest that the chloroplasts are used to meet the nitrogen requirements of the host. Immunolocalization of the nuclear encoded protein, nitrate reductase, supports this hypothesis. This protein is widely distributed in photoautotrophs but is not encoded in eukaryotic protists such as foraminifera.

Compound heterozygosity and nonsense mutations in the α1-subunit of the inhibitory glycine receptor in hyperekplexia - Mark I. Rees; Trevor M. Lewis; Behnaz Vafa; Colin Ferrie; Peter Corry; Fransesco Muntoni; Heinz Jungbluth; John B. Stephenson; Mike Kerr; Russell G. Snell; Peter R. Schofield; Michael J. Owen (Human Genetics, 2001)

Monochromatic ultraviolet light induced damage to Photosystem II efficiency and carbon fixation in the marine diatom Thalassiosira pseudonana (3H) - Joe Grzymski; Cristine Orrico; Oscar M. Schofield (Photosynthesis Research, 2001)

Use of differential fluorescence induction and optical trapping to isolate environmentally induced genes - David Allaway; Neil A. Schofield; Mary E. Leonard; Liliana Gilardoni; Turlough M. Finan; Philip S. Poole (Environmental Microbiology, 2001)
The techniques of differential fluorescence induction (DFI) and optical trapping (OT) have been combined to allow the identification of environmentally induced genes in single bacterial cells. Designated DFI‐OT, this technique allows the in situ isolation of genes driving the expression of green fluorescent protein (Gfp) using temporal and spatial criteria. A series of plasmid‐based promoter probe vectors (pOT) was developed for the construction of random genomic libraries that are linked to gfpUV or egfp . Bacteria that do not express Gfp on laboratory medium (i.e. non‐fluorescent) were inoculated into the environment, and induced genes were detected with a combined fluorescence/optical trapping microscope. Using this selection strategy, rhizosphere‐induced genes with homology to thiamine pyrophosphorylase ( thiE ) and cyclic glucan synthase ( ndvB ) were isolated. Other genes were expressed late in the stationary phase or as a consequence of surface‐dependent growth, including fixND and metX , and a putative ABC transporter of putrescine. This strategy provides a unique ability to combine spatial, temporal and physical information to identify environmental regulation of bacterial gene expression.

Variability in bacterial community structure during upwelling in the coastal ocean - L. J. Kerkhof; M. A. Voytek; R. M. Sherrell; D. Millie; O. Schofield (Hydrobiologia, 1999)

MONITORING A REHABILITATED HARBOR PORPOISE USING SATELLITE TELEMETRY - Andrew J. Westgate; Andrew J. Read; Tara M. Cox; T. David Schofield; Brent R. Whitaker; Kurt E. Anderson (Marine Mammal Science, 1998)

Aluminum and calcium distribution patterns in aluminum-intoxicated roots of Allium cepa do not support the calcium-displacement hypothesis and indicate signal-mediated inhibition of root growth - R. M. S. Schofield; J. Pallon; G. Fiskesjö; G. Karlsson; K. G. Malmqvist (Planta, 1998)

Detection of harmful algal blooms using photopigments and absorption signatures: A case study of the Florida red tide dinoflagellate, Gymnodinium breve - David F. Millie; Oscar M. Schofield; Gary J. Kirkpatrick; Geir Johnsen; Patricia A. Tester; Bryan T. Vinyard (Limnology and Oceanography, 1997)
The utility of photopigments and absorption signatures to detect and enumerate the red tide dinoflagellate, Gymnodinium breve, was evaluated in laboratory cultures and in natural assemblages. The carotenoid, gyroxanthindiester, was an adequate biomarker for G. breve biomass; water‐column concentrations corresponded with cell standing crops and chlorophyll a concentrations during bloom events in Sarasota Bay, Florida. Unlike other carotenoids, the relative abundance of gyroxanthin‐diester did not change throughout a range of physiological states in culture and the gyroxanthin‐diester: chlorophyll a ratio exhibited little variability in a natural assemblage during bloom senescence. Stepwise discriminant analysis indicated that wavelengths indicative of in vivo absorption by accessory chlorophylls and carotenoids could correctly discern spectra of the fucoxanthin‐containing G. breve from spectra of peridinin‐containing dinoflagellates, a diatom, a haptophyte, and a prasinophyte. With the use of a similarity algorithm, the increasing contribution of G. breve was discerned in absorption spectra (and corresponding fourth‐derivative plots) for hypothetical mixed assemblages. However, the absorption properties of chlorophyll c ‐containing algae vary little among taxa and it is difficult to discern the contribution of accessory chlorophylls and carotenoids caused by cell packaging. Therefore, the use of absorption spectra alone may not identify the contribution of a chlorophyll c ‐containing taxon to the composite spectrum of a mixed assemblage. This difficulty in distinguishing among spectra can be minimized by using the similarity algorithm in conjunction with fourth‐derivative analysis.

Mapping of the human adenosine A 2a receptor gene: relationship to potential schizophrenia loci on chromosome 22q and exclusion from the CATCH 22 region - J. Deckert; Markus M. Nöthen; Stephan P. Bryant; Simone Schuffenhauer; Peter R. Schofield; Nigel K. Spurr; Peter Propping (Human Genetics, 1997)

Lactic acid bacteria as vaccine delivery vehicles - J. M. Wells; K. Robinson; L. M. Chamberlain; K. M. Schofield; R. W. F. Le Page (Antonie van Leeuwenhoek, 1996)

Effects of agroforestry-pasture associations on groundwater level and salinity - M. A. Bari; N. J. Schofield (Agroforestry Systems, 1991)

The control of the production process of phytoplankton by the physical structure of the aquatic environment with special reference to its optical properties - Barbara B. Przelin; Max M. Tilzer; Oscar Schofield; Clivia Haese (Aquatic Sciences, 1991)

Organisation of nodulation and nitrogen fixation genes on a Rhizobium trifolii symbiotic plasmid - D. Barry Scott; Chris B. Court; Clive W. Ronson; Kieran F. Scott; John M. Watson; Peter R. Schofield; John Shine (Archives of Microbiology, 1984)